The Enterprise Lingua Franca: A Foundational Framework for Semantic Interoperability and Cross-Functional Cognition - Simon Suwanzy Dzreke; Semefa Elikplim Dzreke (International Journal of Management Science and Application, 2026)
Digital transformation often fails at the conceptual level: Seventy-three percent of cross-functional initiatives fail because the functional mental models don't match up, making it impossible to solve difficult problems like making sustainability profitable. This research identifies a significant deficiency in enterprise interoperability, wherein disparate departmental epistemologies manifested in conflicting interpretations of fundamental constructs such as "customer" or "value" among Marketing, Finance, and Operations—result in strategic incoherence despite technological integration. Technological solutions are inadequate in addressing these profound philosophical gaps. This paper introduces the Enterprise Lingua Franca, a new cognitive framework created through design science research that combines case studies, ontology engineering, and cognitive task analysis to make organizational intelligence more cohesive. It creates the first theory of Cross-Functional Cognition and gives tangible steps for semantic alignment that turn conceptual fragmentation into strategic coherence, which opens up new ways to solve problems.